2022
DOI: 10.1111/ina.13115
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of aerosolized SARS‐CoV ‐2 by 254 nm UV‐C irradiation

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative agent of COVID-19, has spread since January 2020, leading to global health and social crisis. Although early on, the consensus pointed to direct contact and large droplets as the main source of infection, there is now growing evidence that the virus is transmitted by aerosols, 1 which might be even the main route of transmission. 2 Aerosols, as the major transmission route, better explains the superspreading events and the large propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
5
2
Order By: Relevance
“…Compared with the experimental results of the inactivation of aerosolized SARS-CoV-2 conducted by Ruetalo et al (2022) and Ueki et al (2022) ( Table 1 ), the total irradiation dose required for a virus inactivation rate of nearly 99.9% in this study was slightly higher. This result was expected as the emission wavelengths of the LEDs used in the previous studies were 254 nm ( Ruetalo et al, 2022 ) and 265 nm ( Ueki et al, 2022 ), shorter than those used in this study.…”
Section: Resultscontrasting
confidence: 66%
See 3 more Smart Citations
“…Compared with the experimental results of the inactivation of aerosolized SARS-CoV-2 conducted by Ruetalo et al (2022) and Ueki et al (2022) ( Table 1 ), the total irradiation dose required for a virus inactivation rate of nearly 99.9% in this study was slightly higher. This result was expected as the emission wavelengths of the LEDs used in the previous studies were 254 nm ( Ruetalo et al, 2022 ) and 265 nm ( Ueki et al, 2022 ), shorter than those used in this study.…”
Section: Resultscontrasting
confidence: 66%
“…Compared with the experimental results of the inactivation of aerosolized SARS-CoV-2 conducted by Ruetalo et al (2022) and Ueki et al (2022) ( Table 1 ), the total irradiation dose required for a virus inactivation rate of nearly 99.9% in this study was slightly higher. This result was expected as the emission wavelengths of the LEDs used in the previous studies were 254 nm ( Ruetalo et al, 2022 ) and 265 nm ( Ueki et al, 2022 ), shorter than those used in this study. Previous studies in which SARS-CoV-2 solution was dropped onto a Petri dish or well plate also showed that DUV light with a wavelength of 254 nm ( Sabino et al, 2020 ) or 265 nm ( Ueki et al, 2022 ) could inactivate the virus by up to 99.9% at less irradiation dose compared to that with a wavelength of 280 nm ( Inagaki et al, 2020 ).…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…UV-C is already used successfully in various fields, such as medicine, ecology, postharvest technologies etc., alone (Rodgers et al, 2023;Calle et al, 2023;Meneses-Espinosa et al, 2023;Ruetalo et al, 2022;Yemmireddy et al, 2022;Iturralde-García et al 2022;Cruz Mendoza et al, 2022;Berruti et al, 2021;Sorică et al, 2021), or in combination with other methods (e.g. the use of ozone) (Sottani et al, 2023;Dogu-Baykut et al, 2022;Martínez de Alba et al, 2021;Frigerio et al, 2021;Gutiérrez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%